Strategi Komunikasi Partisipatif Masyarakat dalam Pengelolaan Dana Desa di Desa Tanjung Menang, Kabupaten Bengkulu Selatan - Lego Irama; Riswanto Riswanto (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to identify the participatory communication strategies implemented by the community of Tanjung Menang Village, South Bengkulu Regency, in managing Village Funds. Participatory communication plays a strategic role in promoting active community involvement, as reflected in their participation during the planning, implementation, and monitoring stages of village development programs. The study adopts a descriptive qualitative approach, utilizing data collection methods including field observation, in-depth interviews, and document analysis. The research subjects consist of the village head, village officials, members of the Village Consultative Body (BPD), and community members actively involved in the management of Village Funds. The findings reveal that the communication strategies employed include conducting village deliberation meetings, disseminating information through local media, and applying interpersonal communication approaches. These approaches are guided by the five principles of interpersonal communication proposed by Joseph A. Devito, namely openness, empathy, supportiveness, a positive attitude, and equality. Collectively, these principles contribute to the establishment of effective communication in the participatory implementation of village development. This strategy has proven to foster effective two-way communication and enhance community participation. Nevertheless, certain challenges persist, such as the dominance of village officials in decision-making processes and the presence of a